PU-H71 (NSC 750424): a molecular masterpiece that targets HSP90 in cancer and beyond - Saber, Sameh; Abdelhady, Rasha; Elhemely, Mai A.; Elmorsy, Elsayed A.; Hamad, Rabab S.; Abdel-Reheim, Mustafa Ahmed; El-kott, Attalla F.; AlShehri, Mohammed A.; Morsy, Kareem; AlSheri, Ali S.; Youssef, Mahmoud E. (Frontiers in Pharmacology, 2024)
Heat shock protein 90 (HSP90) is a pivotal molecular chaperone with multifaceted roles in cellular health and disease. Herein, we explore how HSP90 orchestrates cellular stress responses, particularly through its partnership with heat shock factor 1 (HSF-1). PU-H71, a selective inhibitor of HSP90, demonstrates significant potential in cancer therapy by targeting a wide array of oncogenic pathways. By inducing the degradation of multiple client proteins, PU-H71 disrupts critical signaling pathways such as MAPK, PI3K/Akt, JAK/STAT, EGFR, and mTOR, which are essential for cancer cell survival, proliferation, and metastasis. We examined its impact on combating triple-negative breast cancer and enhancing the effectiveness of carbon-ion beam therapy, offering new avenues for cancer treatment. Furthermore, the dual inhibition of HSP90A and HSP90B1 by PU-H71 proves highly effective in the context of myeloma, providing fresh hope for patients with this challenging malignancy. We delve into its potential to induce apoptosis in B-cell lymphomas that rely on Bcl6 for survival, highlighting its relevance in the realm of hematologic cancers. Shifting our focus to hepatocellular carcinoma, we explore innovative approaches to chemotherapy. Moreover, the current review elucidates the potential capacity of PU-H71 to suppress glial cell activation paving the way for developing novel therapeutic strategies for neuroinflammatory disorders. Additionally, the present report also suggests the promising role of PU-H71 in JAK2-dependent myeloproliferative neoplasms. Eventually, our report sheds more light on the multiple functions of HSP90 protein as well as the potential therapeutic benefit of its selective inhibitor PU-H71 in the context of an array of diseases, laying the foundations for the development of novel therapeutic approaches that could achieve better treatment outcomes.